2013
DOI: 10.1124/jpet.113.205476
|View full text |Cite
|
Sign up to set email alerts
|

The Grasshopper: A Novel Model for Assessing Vertebrate Brain Uptake

Abstract: The aim of the present study was to develop a blood-brain barrier (BBB) permeability model that is applicable in the drug discovery phase. The BBB ensures proper neural function, but it restricts many drugs from entering the brain, and this complicates the development of new drugs against central nervous system diseases. Many in vitro models have been developed to predict BBB permeability, but the permeability characteristics of the human BBB are notoriously complex and hard to predict. Consequently, one singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…Mayer et al ( 2009 ) identified Mdr65 in a screen for increased BBB permeability to the P-glycoprotein substrate Rhodamine B. Mdr65 is also required at the BBB to protect the brain from various P-glycoprotein xenobiotic substrates, and sensitivity of the Mdr65 mutants to these xenobiotics can be rescued by expression of human P-glycoprotein specifically in the SPG cells, confirming that Mdr65 provides an evolutionarily conserved chemoprotective transport barrier at the invertebrate BBB. Interestingly, recent work in the migratory locust ( Locusta migratoria ) and the desert locust ( Schistocerca gregaria ) has shown that P-glycoprotein-like xenobiotic transporters also provide a transcellular barrier in the locust brain (Nielsen et al, 2011 ; Andersson et al, 2013 ). These findings advance the possibilities of using insect models to study the roles of xenobiotic efflux transporters at the BBB (see below).…”
Section: Molecular Overview Of the Invertebrate Bbbmentioning
confidence: 99%
See 1 more Smart Citation
“…Mayer et al ( 2009 ) identified Mdr65 in a screen for increased BBB permeability to the P-glycoprotein substrate Rhodamine B. Mdr65 is also required at the BBB to protect the brain from various P-glycoprotein xenobiotic substrates, and sensitivity of the Mdr65 mutants to these xenobiotics can be rescued by expression of human P-glycoprotein specifically in the SPG cells, confirming that Mdr65 provides an evolutionarily conserved chemoprotective transport barrier at the invertebrate BBB. Interestingly, recent work in the migratory locust ( Locusta migratoria ) and the desert locust ( Schistocerca gregaria ) has shown that P-glycoprotein-like xenobiotic transporters also provide a transcellular barrier in the locust brain (Nielsen et al, 2011 ; Andersson et al, 2013 ). These findings advance the possibilities of using insect models to study the roles of xenobiotic efflux transporters at the BBB (see below).…”
Section: Molecular Overview Of the Invertebrate Bbbmentioning
confidence: 99%
“…Using the grasshopper system, Nielsen et al ( 2011 ) showed that co-administration of a P-glycoprotein inhibitor with a test P-glycoprotein substrate rendered the BBB more permeable to the P-glycoprotein substrate. Furthermore, Andersson et al ( 2013 ) were able to use this methodology to distinguish P-glycoprotein substrates from non-substrates using liquid chromatography-mass spectrometry to measure the drug content in the brain, either in the absence or presence of a P-glycoprotein inhibitor. This confirmed that P-glycoprotein substrates could be identified using this model system.…”
Section: The Invertebrate Bbb As a Tool For Advancing Therapeutic Intmentioning
confidence: 99%
“…Currently, two insect BBB models have been reported using locusts as model insects (Nielsen et al, 2011;Andersson et al, 2013). An ex vivo model has been developed and allows application of test items directly to entire brains isolated prior to testing.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the use of insect cells from the grasshopper ( Locusta migratoria ) has several key aspectct which are close enough in function for the easy development of in vitro cell cultures which can be used to screen compounds for BBB permeability. [29, 43, 44] Additionally, the zebrafish ( Danio rerio ) has also been used successfully as surrogate model for the BBB permeability studies of compounds. [45, 46]…”
Section: Determining Drug Disposition Into Brainmentioning
confidence: 99%